Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Add the following polynomials. Write your final answer only on the space provided.

In writing the exponent just write it after the variable or use the symbol ^.

Ex. 3x2 write is as 3x2 or 3x^2


1. (2m - 8n + 6) + (4n - 3) =


2. (4y2 - 3xy + x2) + (y2 + 3xy + 3x2) =


3. (8x + 7) + (2x - 6) =


4. (n + 5) + (2n + 7) =


5. (2a + 8) + (a + 2) =


6. (4m + 3n - p) + (2p - 3n + 2m) =


7. (5x2 - 3x + 6) + (x2 + 5x - 15) =


8. (3d - 4e + 6) + (2d +5e + 1) =


9. (5x - 3y) + (10y - 4z) + (2x - 3z) =


10. (2a + 3) + (a - 9) =


Sagot :

Answer:

Step-by-step explanation:

1. (2m - 8n + 6) + (4n - 3) =  2m - 4n +3

2. (4y2 - 3xy + x2) + (y2 + 3xy + 3x2) =  4 -  6xy + 4x2

3. (8x + 7) + (2x - 6) = 10x + 1

4. (n + 5) + (2n + 7) =  3n + 12 which can also be written as common factor;  3(n +4).

5. (2a + 8) + (a + 2) =  3a + 10

6. (4m + 3n - p) + (2p - 3n + 2m) =  6m + p

7. (5x2 - 3x + 6) + (x2 + 5x - 15) =  6x^2 + 2x - 9

8. (3d - 4e + 6) + (2d +5e + 1) =  d - e + 6

9. (5x - 3y) + (10y - 4z) + (2x - 3z) = 7x + 7y - 7z

10. (2a + 3) + (a - 9) = 3a - 6,  common factor 3 (a-2)